Giant Interventricular Septal Hematoma Complicating Left Bundle Branch Pacing - Rohan Trivedi, DO; Eileen Rattigan, MD; Terry D. Bauch, MD; Vernon Mascarenhas, MD; Tariq Ahmad, MD; Faiz A. Subzposh, MD; Pugazhendhi Vijayaraman, MD (JACC: Case Reports, 2023)
An 88-year-old woman underwent atrioventricular node ablation and left bundle branch pacing for atrial fibrillation. She presented to the emergency room several hours after discharge with dyspnea. An echocardiogram revealed a giant interventricular septal hematoma. The patient was successfully treated with conservative medical therapy, with eventual complete resolution of the hematoma. (Level of Difficulty: Intermediate.)